Optimum driving condition for lift creating cylinder by plasma actuators based on wind tunnel evaluation-based design. (2016) - Kanazaki, Masahiro; Matsuno, Takashi; Maeda, Kengo; Kawazoe, Hiromitsu
Kriging-based genetic algorithm (GA) was employed to optimise the parameters of the operating conditions of plasma actuators (PAs). In this study, the lift maximisation problem around a circular cylinder was considered. Two PAs were installed on the upper and the lower side of the cylinder. This problem was similar to the airfoil design, because the circular has potential to work as airfoil due to the control of flow circulation by the PAs with four design parameters. The aerodynamic performance was assessed by wind tunnel testing to overcome the disadvantages of time-consuming numerical simulations. The developed optimisation system explores the optimum waveform of parameters for AC voltage by changing the waveform automatically. Based on these results, optimum designs and global design information were obtained while drastically reducing the number of experiments required compared to a full factorial experiment. An analysis of variance and a scatter plot matrix were introduced for design knowledge discovery. According to the discovered design knowledge, it was found that duty ratios for two PAs are an important parameter to create lift.